2018
DOI: 10.2334/josnusd.17-0190
|View full text |Cite
|
Sign up to set email alerts
|

Nanofilled and conventional resin-modified glass ionomer fillings combined with connective tissue grafts for treatment of gingival recessions with non-carious cervical lesions

Abstract: The aim of this study was to evaluate the clinical root coverage results of subepithelial connective tissue grafts (SCTG) performed on teeth with gingival recessions and non-carious cervical lesions (NCCLs) that were restored with cervical fillings and compare the results of two different filling materials: resin-modified glass ionomer (RMGIC) and nano-ionomer cements (NIC). A total of 54 teeth with Miller Class I gingival recessions with or without NCCLs in 36 patients (28 females, 8 males) were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(51 citation statements)
references
References 25 publications
0
48
0
3
Order By: Relevance
“…Os casos de LCNC associadas à recessão gengival que foram tratados com cirurgia mucogengival de reposicionamento coronal combinada a enxerto de tecido conjuntivo e procedimento restaurador resultaram em melhora do quadro de hipersensibilidade e das condições periodontais e estéticas (12,24). Além disso, a espessura gengival menor que 2 mm pode ser um fator que esteja associado a presença das LCNC, sendo o enxerto gengival livre uma das possibilidades para aumentar a espessura gengival nesses casos (34).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Os casos de LCNC associadas à recessão gengival que foram tratados com cirurgia mucogengival de reposicionamento coronal combinada a enxerto de tecido conjuntivo e procedimento restaurador resultaram em melhora do quadro de hipersensibilidade e das condições periodontais e estéticas (12,24). Além disso, a espessura gengival menor que 2 mm pode ser um fator que esteja associado a presença das LCNC, sendo o enxerto gengival livre uma das possibilidades para aumentar a espessura gengival nesses casos (34).…”
Section: Discussionunclassified
“…Os procedimentos restauradores são alternativas que visam interromper a progressão da LCNC, fortalecendo o remanescente dental, prevenindo o acúmulo de placa e o desenvolvimento da cárie e doença periodontal. Os materiais restauradores comumente utilizados são a resina composta, a resina "flow" e o ionômero de vidro resino-modificado (12,24,26,27). A resina composta foi mais eficiente em relação ao tratamento de hipersensibilidade quando comparado com ionômero de vidro resino-modificado, principalmente entre pacientes jovens.…”
Section: Tratamentounclassified
See 1 more Smart Citation
“…In specific cases, restoration of the site affected by the lesion is necessary 10 . Dursun et al 11 reported in their research that gingival recession and root exposure may be associated with NCCLs and in these cases periodontal treatment is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the advantageous properties of GICs, there were improvements in wear resistance and postoperative sensitivity rate compared to conventional GIC. However, they present mechanical failures when used in areas of load concentration 11,16 .…”
Section: Introductionmentioning
confidence: 99%